A comparative study on enzyme adsorption and hydrolytic performance of different scale corn stover by two-step kinetics. (June 2019) - Zhang, Haiyan; Fan, Zhiliang; Li, Junbao; Han, Lujia
Highlights: The enzyme adsorption and hydrolytic performance of UGCS is better than SGCS. The adsorption quantity depend on the total enzyme loading. Glucose yield of one-step and two-step kinetics are similar at same enzyme loading. The first hydrolysis step contribute more to the total glucose yield. Abstract: To investigate the effect of two-step kinetics on enzyme adsorption and hydrolytic properties of different structural substrates at low enzyme doses. The two-step kinetic experiments of ultrafine grinding (UGCS) and sieve-based grinding corn stover (SGCS) were performed respectively with enzyme loading of 2.5 + 2.5 FPU/g and 5 + 5 FPU/g. The different performance of these two samples were illustrated by characterizing the particle size distribution, SEM and XPS. The results showed that ultrafine grinding can promote the structural properties which is beneficial to adsorption and hydrolysis. The main factors influencing adsorption kinetics are enzyme concentration and the surface cellulose amount. Pre-adsorbed enzyme has no effects on the subsequent enzyme adsorption quantity but produces some small competitive and impeditive effects. The hydrolysis kinetics mainly depend on the structure of the substrate and its complexity of hydrolysis. The two-step hydrolysis didn't promote the total sugar yield under the same enzyme concentration, but the first step contributed more to the total sugar yield.